Confused on recurrence and Big O - algorithm

I know that
T(n) = T(n/2) + θ(1) can be result to O(Log N)
and my book said this is a case of Binary Search.
But, how do you know that? Is it just by the fact that Binary Search cuts the problem in half each time so it is O(Log N)?
And T(n) = 2T(n/2) + θ(1)
why is it that the result is O(N) and not O(Log N) when the algorithm divides in half each time as well.
Then T(n) = 2T(n/2) + θ(n)
can be result to O(N Log N)? I see the O(N) is from θ(n) and O(Log N) is from T(n/2)
I am really confused about how to determine the Big O of an algorithm that I don't even know how to word it properly. I hope my question is making sense.
Thanks in advance!

an intuitive solution for these problems is to see the result when unfolding the recursive formula:
Let's assume Theta(1) is actually 1 and Theta(n) is n, for simplicity
T(n) = T(n/2) + 1 = T(n/4) + 1 + 1 = T(n/8) + 1 + 1 + 1 = ... =
= T(0) + 1 + ... + 1 [logN times] = logn
T'(n) = 2T'(n/2) + 1 = 2(2T'(n/4) + 1) + 1 = 4T'(n/4) + 2 + 1 =
= 8T'(n/4) + 4 + 2 + 1 = ... = 2^(logn) + 2^(logn-1) + ... + 1 = n + n/2 + ... + 1 =
= 2n-1
T''(n) = 2T(n/2) + n = 2(2T''(n/2) + n/2) + n = 4T''(n/4) + 2* (n/2) + n =
= 8T''(n/8) + 4*n/4 + 2*n/2 + n = .... = n + n + .. + n [logn times] = nlogn
To formally prove these equations, you should use induction. Assume T(n/2) = X, and using it - prove T(n) = Y, as expected.
For example, for the first formula [T(n) = T(n/2) + 1] - and assume base is T(1) = 0
Base trivially holds for n = 1
Assume T(n) <= logn for any k <= n-1, and prove it for k = n
T(n) = T(n/2) + 1 <= (induction hypothesis) log(n/2) + 1 = log(n/2) + log(2) = log(n/2*2) = log(n)

I find an easy way to understand these is to consider the time the algorithm spends on each step of the recurrence, and then add them up to find the total time. First, let's consider
T(n) = T(n/2) + O(1)
where n=64. Let's add up how much the algorithm takes at each step:
T(64) = T(32) + 1 ... 1 so far
T(32) = T(16) + 1 ... 2 so far
T(16) = T(08) + 1 ... 3 so far
T(08) = T(04) + 1 ... 4 so far
T(04) = T(02) + 1 ... 5 so far
T(02) = T(01) + 1 ... 6 so far
T(01) = 1 ... 7 total
So, we can see that the algorithm took '1' time at each step. And, since each step divides the input in half, the total work is the number of times the algorithm had to divide the input in two... which is log2 n.
Next, let's consider the case where
T(n) = 2T(n/2) + O(1)
However, to make things simpler, we'll build up from the base case T(1) = 1.
T(01) = 1 ... 1 so far
now we have to do T(01) twice and then add one, so
T(02) = 2T(01) + 1 ... (1*2)+1 = 3
now we have to do T(02) twice, and then add one, so
T(04) = 2T(02) + 1 ... (3*2)+1 = 7
T(08) = 2T(04) + 1 ... (7*2)+1 = 15
T(16) = 2T(08) + 1 ... (15*2)+1 = 31
T(32) = 2T(16) + 1 ... (32*2)+1 = 63
T(64) = 2T(32) + 1 ... (65*2)+1 = 127
So we can see that here the algorithm has done 127 work - which is equal to the input multiplied by a constant (2) and plus a constant (-1), which is O(n). Basically this recursion corresponds to the infinite sequence (1 + 1/2 + 1/4 + 1/8 + 1/16) which sums to 2.
Try using this method on T(n) = 2T(n/2) + n and see if it makes more sense to you.

One visual solution to find the T(n) for a recursive equation is to sketch it with a tree then:
T(n) = number of nodes * time specified on each node.
In your case T(n) = 2T(n/2) + 1
I write the one in the node itself and expand it to two node T(n/2)
Note T(n/2) = 2T(n/4) + 1, and again I do the same for it.
T(n) + 1
/ \
T(n/2)+1 T(n/2)+1
/ \ / \
T(n/4)+1 T(n/4)+1 T(n/4)+1 T(n/4)+1
... ... .. .. .. .. .. ..
T(1) T(1) .......... ............T(1)
In this tree the number of nodes equals
2*height of tree = 2*log(n) = n
Then T(n) = n * 1 = n = O(n)

Related

What is the time complexity of the function T(n)=2T(n/4)+O(1)?(Without masters theorem)

Can anybody please explain the time complexity of T(n)=2T(n/4)+O(1) using recurrence tree? I saw somewhere it says O(n^1/2).
Just expand the equation for some iteration, and use the mathematical induction to prove the observed pattern:
T(n) = 2T(n/4) + 1 = 2(2T(n/4^2) + 1) + 1 = 2^2 T(n/4^2) + 2 + 1
Hence:
T(n) = 1 + 2 + 2^2 + ... + 2^k = 2^(k+1) - 1 \in O(2^(k+1))
What is k? from the expansion 4^k = n. So, k = 1/2 log(n). Thus, T(n) \in O(2^(1/2 log(n) + 1)) = O(sqrt(n)). Note that 2^log(n) = n.

What is the recurrence relation and big O for T(n) = 2T(n-1) + O(N)?

I thought it would be something like this...
T(n) = 2T(n-1) + O(n)
= 2(2T(n-2)+(n-1)) + (n)
= 2(2(2T(n-3)+(n-2))+(n-1))+(n)
= 8T(n-3) + 4(n-2) + 2(n-1) + n
Which ends up being something like the summation of 2i * (n-i), and my book says this ends up being O(2n). Could anybody explain this to me? I don't understand why it's 2n and not just O(n) as the (n-i) will continue n times.
This recurrence has already been solved on Math Stack Exchange. As I solve this recurrence, I get:
T(n) = n + 2(T(n-1))
= n + 2(n - 1 + 2T(n-2)) = 3n - 2 + 2^2(T(n-2))
= 3n - 2 + 4(n - 2 + 2(T(n-3))) = 7n - 10 + 2^3(T(n-3))
= 7n - 10 + 8(n - 3 + 2(T(n-4))) = 15n - 34 + 2^4(T(n-4))
= (2^4 - 1)n - 34 + 2^4(T(n-4))
...and so on.
Effectively the recurrence boils down to:
T(n) = (2n+1) * T(1) − n − 2
See the Math Stack Exchange link for how we arrive at this solution. Taking T(1) to be constant, the dominating factor in the above recurrence is (2(n + 1)).
Therefore, the rate of growth of given recurrence is O(2n).

Determination of computational complexity of sample code

I give you three short codes:
First code:
procedure Proc (n:integer)
begin
if n>0 then
begin
writeln('x')
Proc(n-2)
writeln('*');
Proc(n-2)
end
end
Second code:
procedure Proc (n:integer)
begin
if n>0 then
begin
writeln('*');
Proc(n-1)
end
end
Third code:
procedure Proc (n:integer)
begin
if n>0 then
begin
writeln('x')
Proc(n/2)
writeln('*');
Proc(n/2)
end
end
I would like to know how to determine the computational complexity of each code that I gave, cuz it will help me to better understand.. Can someone write an algorithm for determination of computational complexity of sample code step by step, and do it so that it was possible to apply this algorithm for another examples of codes?
First Question: Assume you know that for the value of n - 2, Proc is called T(n-1) times. Therefore, for the value of n, T(n) = 1 + 2T(n-2), as there would be one call to Proc(n) which would in turn call Proc(n-2) twice. T(n) = 1 + 2T(n-2) is a variant of Tower of Hanoi which is T(n) = 1+2T(n-1). There are proofs here http://en.wikipedia.org/wiki/Tower_of_Hanoi to Show that T(n) = 1+2T(n-1) = 2^n-1. Therefore T(n-1) = 1+2T((n-1)-1)= 1+2T(n-2) = 2^(n-1) -1. In your case T(n) = 1 + 2T(n-2) = 2^(n-1) -1. In other words, subtracting out every other term in the Tower of Hanoi problem saves about half the calls. 2^(n-1) - 1 = 2^n/2 - 1 which is O(2^n).
Second Question: This is easier. T(0) = 1 and T(n) = 1 + T(n-1). You can solve this many different ways, but one is via telescoping:
T(n) = 1 + T(n-1)
T(n-1) = 1 + (n-2)
...
T(1) = 1 + T(0)
Adding up both sides...
T(n) + T(n-1)+...+T(1) = 1 + T(n-1) + ... + 1 + T(0) = n + T(n-1)+...+T(0)
Subtract out like terms.
T(n) = n + T(0) = n + 1. So this is O(n).
Third Question: Similar to the first. T(0) = 1, say we know that for value of n-1, you can see that T(n) = 1 + 2 T(n/2). Note here that T(n) = 1 + 2T(n/2) < n + 2T(n/2).
So solve for 2T(n/2) + n with rolling out the recurrence:
T(n) = 2 T(n/2) + n
T(n/2) = 2 T(n/4) + n/2
So T(n) = 4T(n/4) + n + n
T(n/4) = 2T(n/8) + n/4
So T(n) = 8T(n/8) n + n + n
... It looks like T(n) = 2^kT(n/2^k)+kn for positive k.
Prove it by induction.
k = 1: T(n) = 2 T(n/2)+n which was given. This is our base case.
If true for k-1, show true for k:
T(n) = (2^(k-1))T(n/2^(k-1))+(k-1)n //Inductive hypothesis
T(n/2^(k-1)) = 2 T([n/2^(k-1))]/2)+n/2^(k-1)) //Given recurrence
= 2T(n/2^k)+n/2^(k-1)
=> T(n) = (2^k)T(n/2^k)+ n + (k-1)n = (2^k)T(n/2^k) + kn. So true for k.
T(n) = 2^kT(n/2^k)+kn, choose an appropriate positive k, such as k = ln(n).
T(n) = 2^ln(n) T(n/2^Ln(n)) + nln(n) = nT(1) +nln(n).
T(1) = 1 since Proc would just end. So n(T(1)) + nln(n) = nln(n) + n = O(nln(n)).
Unfortunately, there is not a one-size-fits all procedure for complexity. You have to take it on a case-by-case basis and figure out the problem.

Solving the similar recurrence: T(n) = 3T(n/3) + n/3

Given..
T(0) = 3 for n <= 1
T(n) = 3T(n/3) + n/3 for n > 1
So the answer's suppose to be O(nlogn).. Here's how I did it and it's not giving me the right answer:
T(n) = 3T(n/3) + n/3
T(n/3) = 3T(n/3^2) + n/3^2
Subbing this into T(n) gives..
T(n) = 3(3T(n/3^2) + n/3^2) + n/3
T(n/3^2) = 3(3(3T(n/3^3) + n/3^3) + n/3^2) + n/3
Eventually it'll look like..
T(n) = 3^k (T(n/3^k)) + cn/3^k
Setting k = lgn..
T(n) = 3^lgn * (T(n/3^lgn)) + cn/3^lgn
T(n) = n * T(0) + c
T(n) = 3n + c
The answer's O(n) though..What is wrong with my steps?
T(n) = 3T(n/3) + n/3
T(n/3) = 3T(n/9) + n/9
T(n) = 3(3T(n/9) + n/9) + n/3
= 9T(n/9) + 2*n/3 //statement 1
T(n/9)= 3T(n/27) + n/27
T(n) = 9 (3T(n/27)+n/27) + 2*n/3 // replacing T(n/9) in statement 1
= 27 T (n/27) + 3*(n/3)
T(n) = 3^k* T(n/3^k) + k* (n/3) // eventually
replace k with log n to the base 3.
T(n) = n T(1) + (log n) (n/3);
// T(1) = 3
T(n) = 3*n + (log n) (n/3);
Hence , O (n* logn)
Eventually it'll look like.. T(n) = 3^k (T(n/3^k)) + cn/3^k
No. Eventually it'll look like
T(n) = 3^k * T(n/3^k) + k*n/3
You've opened the parenthesis inaccurately.
These types of problems are easily solved using the masters theorem. In your case a = b = 3, c = log3(3) = 1 and because n^c grows with the same rate as your f(n) = n/3, you fall in the second case.
Here you have your k=1 and therefore the answer is O(n log(n))
This question can be solved by Master Theorem:
In a recursion form :
where a>=1, b>1, k >=0 and p is a real number, then:
if a > bk, then
if a = bk
a.) if p >-1, then
b.) if p = -1, then
c.) if p < -1, then
3. if a < bk
a.) if p >=0, then
b.) if p<0, then T(n) = O(nk)
So, the above equation
T(n) = 3T(n/3) + n/3
a = 3, b = 3, k =1, p =0
so it fall into 2.a case, where a = bk
So answer will be
O(n⋅log(n))

Easy: Solve T(n)=T(n-1)+n by Iteration Method

Can someone please help me with this ?
Use iteration method to solve it. T(n) = T(n-1) +n
Explanation of steps would be greatly appreciated.
T(n) = T(n-1) + n
T(n-1) = T(n-2) + n-1
T(n-2) = T(n-3) + n-2
and so on you can substitute the value of T(n-1) and T(n-2) in T(n) to get a general idea of the pattern.
T(n) = T(n-2) + n-1 + n
T(n) = T(n-3) + n-2 + n-1 + n
.
.
.
T(n) = T(n-k) + kn - k(k-1)/2 ...(1)
For base case:
n - k = 1 so we can get T(1)
=> k = n - 1
substitute in (1)
T(n) = T(1) + (n-1)n - (n-1)(n-2)/2
Which you can see is of Order n2 => O(n2).
Expand it!
T(n) = T(n-1) + n = T(n-2) + (n-1) + n = T(n-3) + (n-2) + (n-1) + n
and so on, until
T(n) = 1 + 2 + ... + n = n(n+1)/2 [= O(n^2)]
provided that T(1) = 1
In pseudo code using iteration:
function T(n) {
int result = 0;
for (i in 1 ... n) {
result = result + i;
}
return result;
}
Another solution:
T(n) = T(n-1) + n
= T(n-2) + n-1 + n
= T(n-3) + n-2 + n-1 + n
// we can now generalize to k
= T(n-k) + n-k+1 + n-k+2 + ... + n-1 + n
// since n-k = 1 so T(1) = 1
= 1 + 2 + ... + n //Here
= n(n-1)/2
= n^2/2 - n/2
// we take the dominating term which is n^2*1/2 therefor 1/2 = big O
= big O(n^2)
Easy Method:
T (n) = T (n - 1) + (n )-----------(1)
//now submit T(n-1)=t(n)
T(n-1)=T((n-1)-1)+((n-1))
T(n-1)=T(n-2)+n-1---------------(2)
now submit (2) in (1) you will get
i.e T(n)=[T(n-2)+n-1]+(n)
T(n)=T(n-2)+2n-1 //simplified--------------(3)
now, T(n-2)=t(n)
T(n-2)=T((n-2)-2)+[2(n-2)-1]
T(n-2)=T(n-4)+2n-5---------------(4)
now submit (4) in (2) you will get
i.e T(n)=[T(n-4)+2n-5]+(2n-1)
T(n)=T(n-4)+4n-6 //simplified
............
T(n)=T(n-k)+kn-6
**Based on General form T(n)=T(n-k)+k, **
now, assume n-k=1 we know T(1)=1
k=n-1
T(n)=T(n-(n-1))+(n-1)n-6
T(n)=T(1)+n^2-n-10
According to the complexity 6 is constant
So , Finally O(n^2)

Resources